The importance of keywords in Molecular Paleontology: exploring the Word Cloud resource for trends representation (Research, Society and Development, 2022)
A lot can be at stake, depending on the choice of words used to describe an emerging science, because terminology affects the way knowledge is developed. Molecular Paleontology is one such area where a wide variety of terms and expressions are being used to refer to their research approaches and objects of study. Thus, this study sought to investigate the frequency of use of recurrent keywords in Molecular Paleontology papers, in order to provide a collection of potential terms that may be useful to guide the choice of descriptors. This is a research carried out with a qualitative-quantitative approach to data. The sample consisted of secondary data, from 4 literature review works, which previously surveyed the papers that claimed findings of paleomolecular traces in different taxonomic groups of vertebrates. Data collection took place through the individual search for keywords and the simple count of their occurrence in each of the analyzed papers. For content analysis, the Word Cloud (WC) graphic method was used from the Infogram platform. In general, 263 keywords were obtained from a total of 45 reviewed papers. Of these, 148 terms were retrieved from 24 papers on non-avian dinosaurs, 79 terms from 14 papers on Cenozoic mammals, 26 terms from 5 papers on Mesozoic birds, and 10 terms from 2 papers on the Pterosauria clade and other Mesozoic marine reptiles. It was observed that the mapping carried out with the support of the WC resource is useful for suggesting terms that can be used as keywords. Thus, this research made it possible, in a preliminary way, to identify terminological and research trends in the field of Molecular Paleontology.